Do Statistical Models Capture the Dynamics of the Magnetopause During Sudden Magnetospheric Compressions?. Issue 4 (13th April 2020) - Staples, F. A.; Rae, I. J.; Forsyth, C.; Smith, A. R. A.; Murphy, K. R.; Raymer, K. M.; Plaschke, F.; Case, N. A.; Rodger, C. J.; Wild, J. A.; Milan, S. E.; Imber, S. M.
Abstract: Under periods of strong solar wind driving, the magnetopause can become compressed, playing a significant role in draining electrons from the outer radiation belt. Also termed "magnetopause shadowing, " this loss process has traditionally been attributed to a combination of magnetospheric compression and outward radial diffusion of electrons. However, the drift paths of relativistic electrons and the location of the magnetopause are usually calculated from statistical models and, as such, may not represent the time‐varying nature of this highly dynamic process. In this study, we construct a database ∼20, 000 spacecraft crossings of the dayside magnetopause to quantify the accuracy of the commonly used Shue et al. (1998,  https://doi.org/10.1029/98JA01103 ) model. We find that, for the majority of events (74%), the magnetopause model can be used to estimate magnetopause location to within ±1 RE . However, if the magnetopause is compressed below 8 RE, the observed magnetopause is greater than 1 RE inside of the model location on average. The observed magnetopause is also significantly displaced from the model location during storm sudden commencements, when measurements are on average 6% closer to the radiation belts, with a maximum of 42%. We find that the magnetopause is rarely close enough to the outer radiation belt to cause direct magnetopause shadowing, and hence rapid outward radial transport of electrons is also required. We conclude that statistical magnetopause parameterizations may not be appropriate during dynamic compressions. We suggest that statistical models should only be used during quiescent solar wind conditions and supplemented by magnetopause observations wherever possible. Key Points: Measured magnetopause location is statistically closer to the Earth than Shue et al. (1998) modeled for storm sudden commencements (SYM‐H ≥15 nT) When the magnetopause is compressed below 8 RE, the average measured location is >1 RE inside of the Shue et al. (1998) model location Extreme magnetopause compressions rarely reach the outer radiation belt, therefore rapid outward radial transport is required to fully explain most shadowing events